The risk management approach to macro-prudential policy - Sulkhan Chavleishvili; Robert F. Engle; Stephan Fahr; Manfred Kremer; Simone Manganelli; Bernd Schwaab (European Central Bank (ECB), 2021)
Macro-prudential authorities need to assess medium-term downside risks to the real economy, caused by severe financial shocks. Before activating policy measures, they also need to consider their short-term negative impact. This gives rise to a risk management problem, an inter-temporal trade-off between expected growth and downside risk. Predictive distributions are estimated with structural quantile vector autoregressive models that relate economic growth to measures of financial stress and the financial cycle. An empirical study with euro area and U.S. data shows how to construct indicators of macro-prudential policy stance and to assess when interventions may be beneficial.
Keywords: G21; C33; 330; Growth-at-risk; stress testing; quantile vector autoregression; financial conditions; macro-prudential policy